Archaeological Survey in Guadalajara: Human Occupation in Central Spain during the Late Pleistocene. (2nd January 2021) - Burke, Ariane; Alcaraz-Castaño, Manuel; Cardineau, Carlos Arteaga; Bisson, Michael; Cuartero, Felipe; Maillo-Fernández, José Manuel; Fuertes-Prieto, Natividad; Yravedra Sainz de los Terreros, Jose
ABSTRACT: The central Meseta is a high plateau located in the heart of the Iberian Peninsula. Abundant evidence of Lower and Middle Palaeolithic occupations of the region contrasts with scarce evidence of a human presence during the early Upper Palaeolithic. On this basis, it has been suggested that climatic downturns triggered the temporary abandonment, or near abandonment, of the central Meseta during the Last Glacial period. We conducted three archaeological surveys in Guadalajara province, located in the southern part of the region, in 2009, 2010, and 2017. Survey results, interpreted in the light of a habitat suitability model, support a hypothesis of climate-driven abandonment (or near-abandonment) of the central plateau during the Last Glacial Maximum and suggest that the Tagus River Valley, which links the Spanish interior to the Atlantic seaboard, was a focus for the Palaeolithic occupation of the region at other times.